Humor and camera view on mobile short-form video apps influence user experience and technology-adoption intent, an example of TikTok (DouYin) - Wang, Yunwen (Computers in human behavior, 2020)
Mobile short-form videos on social media apps are increasingly popular. Human-Computer Interaction (HCI) theories may be extended to short-form video apps to understand and improve app user experience, as well as to persuade new technology-adoption. The present study examined the psychological responses and persuasive outcomes associated with short-form videos on a mobile social media app. In a 2 (low- V.S. high-level humor) X 2 (first- V.S. third-person view) between-subject experimental design, participants (N = 81) were randomly assigned one of the four sets of videos about smart homes; post-viewing, they filled out an online questionnaire. Results of ANCOVA demonstrated significant effects of videos' humor and camera view on the viewer perceptions of Immersion, Social Presence and Entertainment but not on Spatial Presence and Perceptual Realism: Humor had mixed effects on the interaction between users and the mobile app; the first-person camera view elevated viewers' Immersion, Social Presence, Entertainment. As a PROCESS mediation test showed, Social Presence mediated (by 56.78%) the indirect link between the level of humor getting from a video and the viewers’ post-viewing intent to adopt the technology depicted in the video. The study demonstrated values of extending HCI theories to mobile short-form video apps. Implications were discussed in terms of using appropriate humor and camera view for improving user experience and persuading serious agenda. •Mobile short-form videos have the potential to persuade new technology-adoption.•Mobile videos engage viewers' sense of Immersion, Social Presence and Entertainment.•First-person camera view elevates viewers' Immersion, Social Presence, Entertainment.•Humor has mixed effects on the social interaction between users and mobile apps.